How consistently distributed are the socioeconomic differences in severe back morbidity by age and gender? A population based study of hospitalisation among Finnish employees. Issue 4 (23rd March 2006) - Kaila-Kangas, L; Keskimäki, I; Notkola, V; Mutanen, P; Riihimäki, H; Leino-Arjas, P
Abstract : Aims: To study the socioeconomic distribution of severe back morbidity by age and gender, and to examine to what extent the differences in back morbidity between socioeconomic groups are particularly related to manual work in different age groups. Methods: Hospital admissions in 1996 for back disorders of 25–64 year old men (3123 of a total 743 961) and women (3043 of 773 936) from the Finnish Hospital Discharge Register were linked with demographic and socioeconomic data from the 1995 population census. Poisson regression analysis was used to calculate the rate ratios for back related hospitalisation by occupational class and education. The distribution of cases according to occupational status and education was presented in relation to the whole occupationally active workforce by age and gender. Results: Blue-collar (manual) workers had a higher risk of being hospitalised because of back disorders compared with white-collar employees (non-manual) in all age groups among both genders. Manual work versus non-manual work was associated with a 1.3 to 1.4-fold risk (95% CI 1.0 to 1.8) among women and a 1.3 to 1.6-fold risk (95% CI 1.1 to 2.2) among men. The risk of hospitalisation was further inversely associated with educational level within manual and non-manual work in all other age groups except in those aged 55–64 years. Gender related differences were much smaller compared with the socioeconomic ones. Conclusions: Socioeconomic differences in back morbidity leading to hospitalisation were consistent by age and gender. The results suggest that not only the physical strenuousness of work, but also other causes of severe back disorders are clustered around a subject's socioeconomic status, indicated by formal education. This may have implications for prevention and the planning of rehabilitation.